Immunological Properties of Micrococcus lysodeikticus Membranes - Fukui, Yoshio (1971)
Membranes of Micrococcus lysodeikticus possess antigens which are distinct from other cellular components such as cytoplasm, ribosomes, and cell walls. Only a few (two to three) components are found when dissociated membranes are examined by immunodiffusion and immunoelectrophoresis techniques. Membranes treated with 0.3% sodium dodecyl sulfate, 0.3% Triton X-100, trypsin, phospholipase A or C, or by sonic oscillation at pH 9.0, all showed the same pattern (three major bands) when examined against membrane antisera by immunoelectrophoresis. Immunological analysis of fractions isolated by sucrose gradient centrifugation or by polyacrylamide gel electrophoresis suggests that individual components cross-react. Antibodies to adenosine triphosphatase (EC 3.6.1.3) and fast-moving component are not removed by absorption with protoplasts. Removal of antibody to one of the membrane antigens by protoplast absorption indicated a surface location. Glutaraldehyde fixation of protoplasts resulted in the loss of membrane antigens detectable by immunodiffusion.